Dispersal Risks and Decisions Shape How Non-kin Groups Form in a Tropical Silk-Sharing Webspinner (Insecta: Embioptera) - Edgerly, Janice S. (Frontiers in Ecology and Evolution, 2022)
Relying on silk can promote sharing, especially when its presence means life and its absence, quick death. In the case of Embioptera, they construct silken coverings exposed on tree bark in humid and warm environments or in leaf litter and underground in dry habitats. These coverings protect occupants from rain and natural enemies. Of note, adult females are neotenous, wingless and must walk to disperse. Evidence is pulled together from two sources to explore mechanisms that promote the establishment of non-kin groups that typify the neotropical Antipaluria urichi (Clothodidae): (1) a review of relevant information from 40 years of research to identify potential drivers of the facultative colonial system and (2) experimental and observational data exploring how dispersal contributes to group formation. To determine risks of dispersal and decisions of where to settle, adult females were released into the field and their ability to survive in the face of likely predation was monitored. Additional captured dispersers were released onto bark containing silk galleries; their decision to join the silk or to settle was noted. An experiment tested which attributes of trees attract a disperser: vertical or horizontal boles in one test and small, medium, or large boles in another. While walking, experimentally released adult female dispersers experienced a risk of being killed of approximately 25 %. Dispersers orient to large diameter trees and join silk of others if encountered. These results align with observations of natural colonies in that adults and late-stage nymphs join existing colonies of non-kin. Experiments further demonstrated that dispersing females orient to vertical and larger diameter tree-like objects, a behavior that matched the distribution of field colonies. The ultimate reason for the observed dispersion pattern is probably because large trees support more expansive epiphytic algae and lichens (the food for this species), although the impact of food resources on dispersion has not been tested. Finally, further research questions and other webspinner species that warrant a closer look are described. Given that this group of primitively social insects, with approximately 1,000 species known, has remained virtually unstudied, one hope is that this report can encourage more exploration.